Acute hepatitis C virus infection induces anti‐host cell receptor antibodies with virus‐neutralizing properties. Issue 3 (28th July 2015) - Tawar, Rajiv G.; Colpitts, Che C.; Timm, Jörg; Fehm, Tanja; Roggendorf, Michael; Meisel, Helga; Meyer, Nicolas; Habersetzer, François; Cosset, François‐Loïc; Berg, Thomas; Zeisel, Mirjam B.; Baumert, Thomas F.
<x xml:space="preserve">Abstract</x> Hepatitis C virus (HCV) causes persistent infection in the majority of infected individuals. The mechanisms of persistence and clearance are only partially understood. Antibodies (Abs) against host cell entry receptors have been shown to inhibit HCV infection in cell culture and animal models. In this study, we aimed to investigate whether anti‐receptor Abs are induced during infection in humans in vivo and whether their presence is associated with outcome of infection. We established an enzyme‐linked immunosorbant assay using a recombinant CD81‐claudin‐1 (CLDN1) fusion protein to detect and quantify Abs directed against extracellular epitopes of the HCV CD81‐CLDN1 coreceptor complex. The presence of anti‐receptor Abs was studied in serum of patients from a well‐defined cohort of a single‐source HCV outbreak of pregnant women and several control groups, including uninfected pregnant women, patients with chronic hepatitis B and D virus (HBV/HDV) infection, and healthy individuals. Virus‐neutralizing activity of Abs was determined using recombinant cell culture–derived HCV (HCVcc). Our results demonstrate that HCV‐infected patients have statistically significantly higher anti‐CD81/CLDN1 Ab titers during the early phase of infection than controls. The titers were significantly higher in resolvers compared to persisters. Functional studies using immunoadsorption and HCV cell culture models demonstrate that HCV‐neutralizing anti‐receptor Abs are induced in the early phase of HCV infection, but not in control groups. Conclusion: The virus‐neutralizing properties of these Abs suggest a role for control of viral infection in conjunction with antiviral responses. Characterization of these anti‐receptor Abs opens new avenues to prevent and treat HCV infection. (Hepatology 2015;62:726–736)